2019
DOI: 10.1101/724351
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Immunohistochemistry-based taxonomical classification of bladder cancer predicts response to neoadjuvant chemotherapy

Abstract: Platinum-based neoadjuvant chemotherapy (NAC) increases the survival of patients with organ-confined urothelial bladder cancer (UBC). Because not all patients benefit from treatment, NAC has not been widely applied in the clinical setting. There is strong evidence, based on retrospective studies, that patients with Basal/Squamous (BASQ)-like tumours present with more advanced disease and have worse prognosis; global transcriptomics can identify tumour subtypes associated with response to NAC. We aimed to inves… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 34 publications
3
10
0
Order By: Relevance
“…In a retrospective analysis of bladder cancer patients treated with chemoradiation, the impact of IHC-based subtypes on survival and CR to chemoradiation therapy have been assessed by Tanaka et al [19]. More recently, consistent with our experience, Front et al have shown that the patients with basal/squamous (BASQ)-like tumors (KRT5/6/KRT14 high; FOXA1/GATA3 low) were more likely to achieve a CR to NAC (odds ratio, 3.96; p = 0.017) [20]. Compared with our study, similar results were also observed by Front et al regarding the subtype-related survival outcomes.…”
Section: Discussionsupporting
confidence: 65%
“…In a retrospective analysis of bladder cancer patients treated with chemoradiation, the impact of IHC-based subtypes on survival and CR to chemoradiation therapy have been assessed by Tanaka et al [19]. More recently, consistent with our experience, Front et al have shown that the patients with basal/squamous (BASQ)-like tumors (KRT5/6/KRT14 high; FOXA1/GATA3 low) were more likely to achieve a CR to NAC (odds ratio, 3.96; p = 0.017) [20]. Compared with our study, similar results were also observed by Front et al regarding the subtype-related survival outcomes.…”
Section: Discussionsupporting
confidence: 65%
“…Notably, much of the current literature highlights the utility of the same key differentiation markers described in these models and ROC analysis as candidate assays for subtype identification (10,(17)(18)(19)(20). A number of studies propose a combination of two to four luminal and basal protein features such as FOXA1, GATA3, KRT5/6 and KRT14 (10,19,20) for bladder cancer subtyping.…”
Section: Discussionmentioning
confidence: 99%
“…Work from the Lund group has identified further prognostic differences amongst the luminal subtypes, such that the GU subtype experiences a worse prognosis relative to its Uro counterpart. Molecular subtypes have also been associated with response to neoadjuvant chemotherapy and immune checkpoint blockade (3,(8)(9)(10)(11)(12)(13). These predictive and prognostic associations indicate potential clinical applications of subtyping.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations